Swelling behavior of bisensitive interpenetrating polymer networks for microfluidic applications. Issue 25 (13th May 2016) - Krause, A. T.; Zschoche, S.; Rohn, M.; Hempel, C.; Richter, A.; Appelhans, D.; Voit, B.
Abstract : A bisensitive IPN and its characterization via a modified Tanaka kinetics and balanced swelling ratios are presented. Abstract : Bisensitive interpenetrating polymer network (IPN) hydrogels of temperature sensitive net -poly( N -isopropylacrylamide) and pH sensitive net -poly(acrylic acid- co -acrylamide) for microfluidic applications were prepared via a sequential synthesis using free radical polymerization. The IPN indicated a suitable reversible alteration of swelling in response to the change in pH and temperature. The adequate change of the hydrogel volume is a basic requirement for microfluidic applications. Using the introduced correction factor f, it is possible to determine the cooperative diffusion coefficient ( D coop ) of cylindrical samples at any aspect ratio. The determined cooperative diffusion coefficient allowed the evaluation of varying swelling processes of different network structures. The presence of the second sub-network of the IPN improved the swelling behaviour of the first sub-network compared to the individual networks.